Si è sempre detto così? Sessismo linguistico nei manuali di italiano L2/LS dagli anni 1970 ad oggi - Frabotta, Simona; Pauletto, Franco (Sage, 2024)
In recent years, feminist linguistic research in Italy has focused on the use of feminine forms of names designating professions and titles. Historically, professional terminology was exclusively masculine, a fact that reflected women's limited access to the job market. However, the increased presence of women in the labour market has highlighted the inadequacy and sexist nature of this language, underscoring the need for an appropriate definition of women's roles. The aim of this study is to look at the presence of feminine agentives in L2/LS Italian textbooks published from the 1970s to the present to ascertain whether there has been any development that linguistically reflects the increased presence and relevance of women in the workforce. The results indicate a continued underrepresentation of women and a tendency for female characters to be associated with humble and less specialized occupations. In textbooks published since the 2010s, women seem to occupy more relevant job roles, but the tendency is to do so by resorting to the unmarked masculine. More recent textbooks published in the 2020s, on the other hand, show a clear trend toward the use of feminine forms even for jobs traditionally dominated by male figures (“avvocata”, “giardiniera”, “controllora”, etc.). Overall, while these educational resources until recently did not seem to reflect either Italian social reality or linguistic guidelines – which require the use of feminine names of professions in accordance with the rules of the Italian language – more recent developments show an emerging awareness of gender issues that bodes well for the future.
Política de acceso abierto tomada de: https://openpolicyfinder.jisc.ac.uk/id/publication/24718
Geografia e Storia delle Grammatiche dell'Italiano (GeoStoGrammIt) (PRIN 2020)
Keywords: Sexismo en el lenguaje; Italiano - Estudio y enseñanza; Sessismo linguistico; Lavoro; Glottodidattica; Manuali; Linguistica diacronica